(untitled) (International journal of artificial intelligence, 2024)
This article reflects on the history of the formation and urbanization of the ancient city of Karshi in the distant past. It is based on the fact that the appearance of the city of Karshi has been constantly changing over a long period of time. The article also provides detailed information on the development and irrigation of the city of Karshi.